Ice-dance Technical Reference
This section was compiled and created to give ice dancing fans a better understanding of the sport by providing detailed information including rules, terminology, and descriptions of compulsory dance rhythms (with patterns). We've also included a history of compulsory dance rhythms and patterns. Compulsory dance patterns and descriptions are featured on this site are from the USFSA and the ISU rule books. A special thanks to these organizations for granting ice-dance.com permission to quote from the rule books and feature the patterns. If you know of any changes to what's printed here, we would love to hear from you! Information on dance patterns and rules can also be found in Blades on Ice's "A Spectators Guide to Competitive Ice Skating." PATTERNS & TERMINOLOGY Compulsory Dance Descriptions & Patterns Definitions of Ice Dancing Terms Compulsory & Original Dance Rhythms (1968-2002) Compulsory & Original Dance Rhythms (2003 & future seasons)